Digest: Evolution and maintenance of androdioecy in a haplodiploid insect. (30th September 2021) - Molinier, Cécile; Boyer, Loreleï; Villamil, Nora
Abstract: The coexistence of hermaphrodites and males (androdioecy) is rare in both plants and animals and has hitherto remained unknown in insects. Mongue et al. report a new case of androdioecy in the invasive haplodiploid insect Icerya purchasi, in which hermaphrodites can only self‐fertilize, but occasionally mate with males. Revealingly, I. purchasi shares several features with other androdioecious species such as the consequences of evolution from separate sexes, low outcrossing rates, and its colonizing habit.